STAKEHOLDER PEMILU DALAM MENYUKSESKAN PELAKSANAAN PEMILU SERENTAK 17 APRIL TAHUN 2019 - Wilar, Wiesje Fenny (HOLISTIK, Journal Of Social and Culture, 2019)
To ensure the achievement of business goals and objectives as stated in the opening of the State Constitution of the Republic of Indonesia year 1945 general election need to be executed to generate the representatives of the people and the Government of the Democratic based on Pancasila and the 1945 Constitution. Whether a successful implementation process concurrent general elections April 17, 2019 as a National agenda is set not just on one side only, but will be the shared responsibility of all electoral stakeholders in the unity of the Republic of Indonesia which we love do we as Governments or as the organizer of the election (Election Commission, BAWASLU, DKPP); The participants of the election (political party for the elections of members of Parliament, members of Provincial, Regency/City DPRD members; individuals for DPD, and candidates proposed by political parties or political parties combined). The Government should give a trial on all the people, the atmosphere is conducive in the implementation of the election does not belong to a group of interests, Government Officials in this case should be an example and a role model in the Westernization of Pancasila. Political parties serve as a means of political education and increasing participation but in reality a lot of the behavior and attitudes of assumed the party who did not educate the public, the occurrence of dualism leadership marked the existence of conflict internal party; or partner aspiring to grow increasing the political participation of society only offers a program with the promise – a promise that pompous in the campaign by not considering the ability of the nation's economy. Organizers in organizing general elections must have a high commitment, high integrity and independent to achieve democracy through the elections with emphasis on principles of organizing elections that independent, Honest, fair, Orderly, legal certainty, the public interest, Proportionality, openness, professionalism, accountability, efficiency, effective, and accessibility as a people's mandate through electoral legislation. Keywords: constitution, stakeholder, electoral